2012
DOI: 10.1111/j.1365-2265.2011.04218.x
|View full text |Cite
|
Sign up to set email alerts
|

Four polymorphisms of the CAPN 10 gene and their relationship to polycystic ovary syndrome susceptibility: a meta‐analysis

Abstract: This is the first report on the association between CAPN 10 UCSNP-63 and PCOS in genotype, with homozygous carriers and recessive model being protective factors. Additionally, insert allele and recessive model of UCSNP-19 are protective factors, while deletion allele and heterozygous genotype are risk factors for PCOS development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
1
8
2
Order By: Relevance
“…The CAPN10 gene has multiple SNPs. In a meta-analysis study, the association of UCSNP-63 and UCSNP-19 polymorphisms with PCOS was proved [ 45 ]. In another meta-analysis study, the role of UCSNP-45 as well as UCSNP-63 and UCSNP-19 polymorphisms was confirmed as the risk factors for PCOS, especially in Asian women [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The CAPN10 gene has multiple SNPs. In a meta-analysis study, the association of UCSNP-63 and UCSNP-19 polymorphisms with PCOS was proved [ 45 ]. In another meta-analysis study, the role of UCSNP-45 as well as UCSNP-63 and UCSNP-19 polymorphisms was confirmed as the risk factors for PCOS, especially in Asian women [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although there is no significant association between individual polymorphisms of CAPN10 and PCOS, neither the haplotype nor the diplotypes of this gene showed significant associations with PCOS in African-American [48], Korean [93] or Indian populations [34]. A recent meta-analysis using 11 case control studies demonstrated that the CAPN10 UCSNP-63 homozygous allele and the UCSNP-19 insert allele are protective factors for PCOS [77].…”
Section: Calpain-10 (Capn10)mentioning
confidence: 98%
“…However, the results remain controversial. There have been two meta-analyses that examined the association between CAPN10 gene polymorphisms and PCOS risk in 2012 and 2013, respectively ( Huang et al, 2012 ; Shen et al, 2013 ). The meta-analysis by Huang et al ( Huang et al, 2012 ) identified significant associations between UCSNP-19, and -63 and PCOS risk among UCSNP-19, -43, -44 and -63.…”
Section: Introductionmentioning
confidence: 99%